Transcriptome Signature of Vγ9Vδ2 T Cells Treated With Phosphoantigens and Notch Inhibitor Reveals Interplay Between TCR and Notch Signaling Pathways - Madhok, Ayush; Bhat, Sajad Ahmad; Philip, Chinna Susan; Sureshbabu, Shalini Kashipathi; Chiplunkar, Shubhada; Galande, Sanjeev (Frontiers in Immunology, 2021)
Gamma delta (γδ) T cells, especially the Vγ9Vδ2 subtype have been implicated in cancer therapy and thus have earned the spotlight in the past decade. Although one of the most important properties of γδ T cells is their activation by phosphoantigens which are, intermediates of the Mevalonate and Rohmer pathway of isoprenoid biosynthesis, such as IPP and HDMAPP respectively, the global effects of such treatments on Vγ9Vδ2 T cells remain elusive. Here, we used the high-throughput transcriptomics approach to elucidate the transcriptional changes in human Vγ9Vδ2 T cells upon HDMAPP, IPP and anti-CD3 treatments in combination with IL2 cytokine stimulation. These activation treatments exhibited a dramatic surge in transcription with distinctly enriched pathways. We further assessed the transcriptional dynamics upon inhibition of Notch signaling coupled with activation treatments. We observed that the metabolic processes are most affected upon Notch inhibition via GSI-X. The key effector genes involved in gamma-delta cytotoxic function were downregulated upon Notch blockade even in combination with activation treatment, thus, showing suggesting a transcriptional interplay crosstalk between TCR signaling and Notch signaling in Vγ9Vδ2 T cells. Collectively, we show demonstrate how the effect of the activation of TCR signaling by phosphoantigens or anti-CD3 changes on the transcriptional status of Vγ9Vδ2 T cells along with IL2 stimulation. We further show that, and how the blockade of Notch signaling can antagonistically affects this activation.